Community’s experiential knowledge on the development of rural tourism competitive advantage: a study on Kampung Semadang – Borneo Heights, Sarawak - Chee, Hua Chin; Su-Zhuang, Susan Thian; Lo, May-Chiun (Emerald Publishing Limited, 2017)
Purpose - Rural tourism has emerged as one of the potential economic contributors to the country’s economic growth. To this extent, tourism stakeholders are aware of the rural tourism destination competitiveness where the development should be aligned with the objectives in order to achieve destination competitive advantage. Given the importance of studying factors that contribute to the development of rural tourism competitive advantage, the present study proposed a research framework by identifying six predictors from the local community based on their experiential knowledge. Design/methodology/approach - Data were gathered through a structured questionnaire survey where 144 respondents comprising local communities from Kampung Semadang – Borneo Heights, Sarawak, Malaysia were involved. To assess the developed model, SmartPLS 2.0 (M3) was applied based on path modelling (measurement model assessment) followed by bootstrapping analysis (structural model assessment). Findings - Interestingly, the findings revealed that the communities believed economic, socio-cultural, and environmental impacts significantly contributes to the development of rural tourism competitive advantage. Additionally, communities from Kampung Semadang viewed that both community knowledge and support for tourism greatly affect the development of rural tourism destination competitive advantage. Surprisingly, there was no significant relationship between stakeholder involvement and rural tourism competitive advantage. Practical Implications - From a practical point of view, the findings of the study provide valuable information to tourism stakeholders and policy planners about the importance of tri-dimensional tourism impacts as well as community knowledge and support in the development of rural tourism destination competitive advantage. In line with policy development or planning for rural tourism development, the tourism stakeholders should pay more concern on the tri-dimensional impacts, the importance of community knowledge about tourism, and gaining the community support for tourism development in order to achieve the goal of competitiveness. Originality/value – There is lack of study in investigating the development of rural tourism competitive advantage with a holistic framework. This paper studies the intended or unintended economic, socio-cultural and environmental impacts triggered by the tourism activities. This study has also investigated the local communities’ knowledge and supports towards tourism as the community efforts determine the success of a destination management, especially in the rural area. Stakeholder involvement was also examined as the collaboration among relevant parties to create competitive advantage is essential to achieve sustainable rural tourism.